1962
DOI: 10.1084/jem.115.3.655
|View full text |Cite
|
Sign up to set email alerts
|

Antibody Formation

Abstract: Quantitative studies of antibody formation in experimental animals have been facilitated by the use of labeled proteins (1, 2). After equilibration following intravenous injection, labeled antigen is eliminated from the circulation in two exponential phases: the first and slower rate is due to non-immune catabolism; the second and rapid decline is caused by the production and release into the circulation of specific antibody (3, 4).In this study, guinea pigs have been injected with relatively minute amounts of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
41
2

Year Published

1962
1962
2013
2013

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 121 publications
(50 citation statements)
references
References 19 publications
7
41
2
Order By: Relevance
“…Distinctions between primary and secondary responses are sometimes muddied but can often be drawn with respect to parameters such as rapidity, magnitude and antigen sensitivity, class and combining affinity of immunoglobulin produced, sequence of immunoglobulin production, effect of adjuvants, and susceptibility to a variety of suppressants including antibody to the antigen, anti-lymphocyte antibody, and X-irradiation (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18). The ability to mount a secondary response may be ascribed to immunological memory.…”
Section: Discussionmentioning
confidence: 99%
“…Distinctions between primary and secondary responses are sometimes muddied but can often be drawn with respect to parameters such as rapidity, magnitude and antigen sensitivity, class and combining affinity of immunoglobulin produced, sequence of immunoglobulin production, effect of adjuvants, and susceptibility to a variety of suppressants including antibody to the antigen, anti-lymphocyte antibody, and X-irradiation (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18). The ability to mount a secondary response may be ascribed to immunological memory.…”
Section: Discussionmentioning
confidence: 99%
“…Antibody production and immature plasma cell proliferation in the red pulp of the spleen also diminish later in the primary response (day 7) (1) than in the secondary (day 4), when the booster injection is given 10 days after the primary injection. There is, thus, an apparent difference between the response to a simple protein antigen, as used here, and to bacteriophage antigens, since it has recently been shown (26) that rates of antibody production in primary and secondary response to a bacteriophage antigen are quite similar. An interesting aspect of the differences between primary and secondary responses is that the antibody formed in the primary response, both to bacteriophage (26) and to other antigens (27,28), is 19S gamma globulin, while in the secondary it is 7S gamma globulin.…”
Section: Discussionmentioning
confidence: 97%
“…Many viruses appear to be cleared from the serum of noDimmune mice by the reticuloendothelial system (8). Specific antibody has been shown to enhance the rate of clearance of infective virus particles from the blood (9,10). That noDimmune clearance mechanisms can be altered has been demonstrated by Brunner et al (11) who showed that an intravenous injection of thorotrast decreases the clearance of Newcastle disease virus (NDV) in nonimmune mice.…”
Section: Discussionmentioning
confidence: 99%